2004
DOI: 10.1073/pnas.0403649101
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's brains harbor somatic mtDNA control-region mutations that suppress mitochondrial transcription and replication

Abstract: Defects in mitochondrial oxidative phosphorylation have frequently been associated with Alzheimer's disease (AD), and both inherited and somatic mtDNA mutations have been reported in certain AD cases. To determine whether mtDNA mutations contribute more generally to the etiology of AD, we have investigated the sequence of the mtDNA control region (CR) from AD brains for possible disease-causing mutations. Sixty-five percent of the AD brains harbored the T414G mutation, whereas this mutation was absent from all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
360
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(376 citation statements)
references
References 52 publications
13
360
2
1
Order By: Relevance
“…The proximity of the 414 nucleotide to the origin of heavy-strand replication could make this region particularly vulnerable to free radical mediated damage during mtDNA replication because of the prolonged period of time that this region will be in single-strand form. This connection to a stressful environment is also evident given the identification of the T414G mutation in the brains of Alzheimer's patients (Coskun et al ., 2004); a pathological condition known to be associated with mitochondrial oxidative stress. Interestingly, distinct mtDNA mutations in this region of the genome have been shown to accumulate with age in skeletal muscle, demonstrating a tissue-specific pattern of occurrence (Wang et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The proximity of the 414 nucleotide to the origin of heavy-strand replication could make this region particularly vulnerable to free radical mediated damage during mtDNA replication because of the prolonged period of time that this region will be in single-strand form. This connection to a stressful environment is also evident given the identification of the T414G mutation in the brains of Alzheimer's patients (Coskun et al ., 2004); a pathological condition known to be associated with mitochondrial oxidative stress. Interestingly, distinct mtDNA mutations in this region of the genome have been shown to accumulate with age in skeletal muscle, demonstrating a tissue-specific pattern of occurrence (Wang et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There is the distinct possibility of mutations in the mtDNA control region (CR), which is the origin of replication of the mitochondrial genome and drives the copy number of mtDNA. [61][62][63] Variations in nDNA genes involving chaperone, apoptotic and oxidative phosphorylation pathways have also been shown in studies of bipolar disorder. 51,60,[64][65][66][67][68] There might be common regulatory motifs in the promoter regions for some of the oxidative phosphorylation genes as many of these genes appear to be coregulated in multiple studies.…”
mentioning
confidence: 92%
“…A number of studies reported a reduction in COX activity and an increase in oxidative stress in brain tissues and platelets from AD patients (7-10). More recently, the associations of heteroplasmic mutations in the mtDNA control region and point mutations in mtDNA-encoded COX subunits with sporadic AD cases were reported (11,12), supporting the contribution of mtDNA mutations and COX reduction to the development of AD. However, conflicting evidence exists, and a recent haplogroup association study and case-control comparison of complete coding sequences of mtDNA between AD patients and age-matched controls reached a conclusion that mtDNA mutations do not play a major role in the development of AD (13,14).…”
mentioning
confidence: 99%